Histological evaluation of direct pulp capping by using of calcium hydroxide and octacalcium phosphate in cats dental pulp - Eshagh Ali Saberi; Fereydoon Sargolzaei Aval; Arab Mohammad Reza Mohammad Reza; Seddighe Ebrahimipour (Tehran University of Medical Sciences, 2013)
Background and Aims: The purpose of this study was to evaluate the tissue responses to octacalcium phosphate (OCP) and calcium hydroxide (CH) used as direct pulp capping (DPC) materials in cat teeth.   Materials and Methods: 72 premolar teeth of 9 cats were selected and divided into 3 groups (Two experimental and one control group). After the cats had been anesthetized, the pulp were exposed and capped directly with OCP, CH or no capping material as control group. The cavities of all three groups were filled with Glass ionomer cement (GI). Histological evaluations were performed at two, four and eight weeks after pulp capping. After tissue preparation procedures, paraffin blocks were prepared. After preparation and staining of the sections, the relevant variables were measured by optical microscope. The results were analyzed using Mann-Whitney U and Chi-square tests ( α =0.05).   Results: Two weeks after pulp capping, all specimens in three groups showed mild to sever inflammation. The formation of hard tissue (dentinal bridge) at in the exposed areas of the experimental groups was more noticeable for calcium hydroxide than that of octacalcium phosphate group. These differences were statistically significant (P<0.001). At four weeks, hard tissues were observed in both groups which were more evident for the CH group and there were statistically significant difference between two experimental groups (p0.05), but hard tissues continuity were better for in the OCP than that of the CH.   Conclusion: It seems that the formation of hard tissue in CH because of its porosities had a worse percentage in sealing of the pulp than the OCP .